Model Pemberdayaan Ekonomi Perempuan Papua di Kampung Senamai - Waromi, Eirene Margretha (Program Doktor Ilmu Sosial Universitas Cenderawasih, 2023)
The division of roles between men and women is expected to have the value of equality rather than inequality as a result of socio-cultural construction in society. The importance of socio-cultural changes influences the development and participation of women in the economy. For this reason, an approach is needed through appropriate interventions in facing the challenges of women in the economy. This research uses qualitative methods, data collection includes observation and in-depth interviews, data analysis through data reduction stages, data presentation and drawing conclusions. The research findings show that indicators of social change in the community of Senamai Village, Yokari District, also influence the economic empowerment of Papuan women living in the coastal area of Senamai Village. Based on the socio-cultural changes and economic empowerment situation, as well as various challenges in promoting women's adaptation process in the era of modernization from a system economy to a market economy, an appropriate intervention model is needed to implement economic empowerment for Papuan women in coastal areas based on a socio-cultural change approach.